2003
DOI: 10.1073/pnas.0336398100
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of acyl CoA:cholesterol acyltransferase 2 prevents atherosclerosis in apolipoprotein E-deficient mice

Abstract: Deficiency of acyl CoA:cholesterol acyltransferase 2 (ACAT2) in mice results in a reduction in cholesterol ester synthesis in the small intestine and liver, which in turn limits intestinal cholesterol absorption, hepatic cholesterol gallstone formation, and the accumulation of cholesterol esters in the plasma lipoproteins. Here we examined the contribution of ACAT2-derived cholesterol esters to atherosclerosis by crossing ACAT2-deficient (ACAT2 -/-) mice with apolipoprotein (apo) E-deficient (ApoE -/-) mice, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
141
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(147 citation statements)
references
References 41 publications
3
141
2
1
Order By: Relevance
“…We identified other genes related to lipid metabolism whose expression is up-regulated in the liver of NFR-treated mice, including Soat2 (also abbreviated as Acat2), which was also found among the top genes up-regulated in MEFs in an eIF2α phosphorylation-dependent manner. This enzyme contributes to cholesterol ester synthesis in the small intestine and liver and therefore can promote hypercholesterolaemia and atherosclerosis (59), two metabolic disturbances often observed in HIV-PI-treated patients. All together these data further show that the ISR is a key metabolic regulator that can affect multiple pathways related to lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…We identified other genes related to lipid metabolism whose expression is up-regulated in the liver of NFR-treated mice, including Soat2 (also abbreviated as Acat2), which was also found among the top genes up-regulated in MEFs in an eIF2α phosphorylation-dependent manner. This enzyme contributes to cholesterol ester synthesis in the small intestine and liver and therefore can promote hypercholesterolaemia and atherosclerosis (59), two metabolic disturbances often observed in HIV-PI-treated patients. All together these data further show that the ISR is a key metabolic regulator that can affect multiple pathways related to lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand ACAT2 is expressed exclusively in lipoprotein-producingcells such as intestinal enterocytes and hepatocytes in the liver (7,8), and plays a gatekeeper role in the production of atherogenic apoB-containing lipoproteins (6 -10). In support of this concept, when compared with wild type controls, ACAT2-deficient mice have reduced cholesterol absorption (11)(12)(13)(14), are depleted in hepatic cholesteryl esters (CE) (7)(8)(9)(10)(11)(12)(13)(14), and are protected against diet-induced gallstone formation and atherosclerosis (10,11,15). Importantly, the hepatic storage and secretion of CE into apoB-containing lipoproteins is virtually absent in mice lacking ACAT2 (9 -14), indicating that ACAT2 is the sole cholesterol-esterifying enzyme in mouse liver.…”
mentioning
confidence: 99%
“…13 Willner et al recently showed that the enrichment of cholesterol of LDL is another important risk factor for atherosclerosis; triglyceride-rich apoB-containing lipoproteins are not as atherogenic as those containing cholesteryl esters. 14 The authors proposed that the inflammatory response in atherosclerosis occurs primarily in response to toxicity from cholesterol accumulation in lesions. 14 However, it has also been shown that the triglyceride content of LDL are reciprocally related to the number of exposed free lysine amino groups of apoB100.…”
mentioning
confidence: 99%